The Effects Of Early Menarche On Sexual And Reproductive Health: A Scoping Review - Hanny Wulandari; Dwi Ernawati; Sri Lestari (Universitas 'Aisyiyah Yogyakarta, 2021)
Early menarche in adolescent girls has an effect on how quickly they come into contact with sexual life. This may have an impact on the increased incidence of unintended pregnancy, increased childbirth and abortion in adolescents. The condition of adolescents who are too young at menarche and poor reproductive health status will create problems with their menstruation, especially when the right sources of reproductive health information are not fully utilized. The aim of this scoping review is to interpret the effects of early menarche on sexual and reproductive health. The Scoping Review method was carried out using the following steps; 1) identifying research questions; 2) identifying relevant studies, through the Pubmed, Ebsco, and Wiley databases. In the search for articles, the keywords used are Effect OR Outcomes AND Menarche OR Menstruation OR Menstrua * OR menses OR